2009
DOI: 10.1021/jm901351f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, X-ray Structure, and Pharmacokinetics of Aminopyrimidine c-jun-N-terminal Kinase (JNK) Inhibitors

Abstract: Given the significant body of data supporting an essential role for c-jun-N-terminal kinase (JNK) in neurodegenerative disorders, we set out to develop highly selective JNK inhibitors, with good cell potency, and good brain penetration properties. The structure activity relationships (SAR) around a series of aminopyrimidines was evaluated utilizing biochemical and cell- based assays to measure JNK inhibition, and brain penetration in mice. Microsomal stability in three species, P450 inhibition, inhibition of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 46 publications
6
92
0
Order By: Relevance
“…Previous work in our laboratory demonstrated that JNK signaling contributes to the generation of ROS during stress. We found that INS-1 insulinoma rat cells treated with streptozotocin produced ROS, and use of a highly selective small molecule inhibitor of JNK (SR-3562 or Compound 9l) prevented ROS production (19). Congruent with our results, JNK-dependent ROS generation was observed in TNF-␣ stimulated murine embryonic fibroblasts (MEFs) lacking functional NF-B signaling (20).…”
supporting
confidence: 51%
See 3 more Smart Citations
“…Previous work in our laboratory demonstrated that JNK signaling contributes to the generation of ROS during stress. We found that INS-1 insulinoma rat cells treated with streptozotocin produced ROS, and use of a highly selective small molecule inhibitor of JNK (SR-3562 or Compound 9l) prevented ROS production (19). Congruent with our results, JNK-dependent ROS generation was observed in TNF-␣ stimulated murine embryonic fibroblasts (MEFs) lacking functional NF-B signaling (20).…”
supporting
confidence: 51%
“…It has been proposed that JNK can induce ROS generation (19,20,37), and that this amplification of superoxide production is part of the cellular response to mitochondrial factors released early in cellular stress (37). This observation is born out in our experiment involving the incubation of active JNK with mitochondria from unstressed and stressed JNK null MEFs.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Based on the structural information and binding analysis done by other authors for several JNK variants (35)(36)(37)(38)(39)(40)(41)(42), we expected Langmuirian kinetics with 1:1 stoichiometry for the studied interactions. Some of the factors that can cause deviations from pseudo-first order approximation of binding data include: mass transfer effects, immobilized ligand density, inhomogeneity of immobilized ligand or soluble analyte, immobilization chemistry, and rebinding of dissociated analyte (43).…”
Section: -10mentioning
confidence: 68%